2020
DOI: 10.1002/ange.202000929
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor/Covalent‐Organic‐Framework Z‐Scheme Heterojunctions for Artificial Photosynthesis

Abstract: A strategy to covalently connect crystalline covalent organic frameworks (COFs) with semiconductors to create stable organic–inorganic Z‐scheme heterojunctions for artificial photosynthesis is presented. A series of COF–semiconductor Z‐scheme photocatalysts combining water‐oxidation semiconductors (TiO2, Bi2WO6, and α‐Fe2O3) with CO2 reduction COFs (COF‐316/318) was synthesized and exhibited high photocatalytic CO2‐to‐CO conversion efficiencies (up to 69.67 μmol g−1 h−1), with H2O as the electron donor in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“… 93 Lan et al developed an organic (COFs)–inorganic (α‐Fe 2 O 3 ) Z‐scheme heterojunctions photoelectrode (Figure 17(C)). 151 This heterojunction photoanode is the first reported and confirmed that the effective covalent coupling between organic framework and semiconductor enables the effective transport of photogenerated electrons between organic functional groups and the semiconductor. Liu et al designed and fabricated the MOF‐derived p‐Cu 2 O/n‐Ce‐Fe 2 O 3 heterojunction photoanode with more surface reaction active sites and large surface area (Figure 17(D)).…”
Section: Interfacial Engineering Of the Hematite Photoanodesupporting
confidence: 55%
See 1 more Smart Citation
“… 93 Lan et al developed an organic (COFs)–inorganic (α‐Fe 2 O 3 ) Z‐scheme heterojunctions photoelectrode (Figure 17(C)). 151 This heterojunction photoanode is the first reported and confirmed that the effective covalent coupling between organic framework and semiconductor enables the effective transport of photogenerated electrons between organic functional groups and the semiconductor. Liu et al designed and fabricated the MOF‐derived p‐Cu 2 O/n‐Ce‐Fe 2 O 3 heterojunction photoanode with more surface reaction active sites and large surface area (Figure 17(D)).…”
Section: Interfacial Engineering Of the Hematite Photoanodesupporting
confidence: 55%
“…(C) Band‐structure diagram for COF‐318, TiO 2 , Bi 2 WO 6 , and α‐Fe 2 O 3 . Source: Reprinted with permission from Reference 151 copyright (2020) John Wiley and Sons. (D) Schematic illustration of PEC water splitting mechanism for the FeOOH/Cu 2 O/Ce‐Fe 2 O 3 photoanode.…”
Section: Interfacial Engineering Of the Hematite Photoanodementioning
confidence: 99%
“…Notably, the rate is superior to metal-containing TT-COF-Zn (2.055 μmol g −1 h −1 ) 64 and hybrid COF-318-TiO 2 catalyst (69.67 μmol g −1 h −1 ). 68 The system retains a rate of 95.5 μmol h −1 g −1 after three cycles, while the selectivity is >98%. This performance stems from the donor-acceptor skeleton that improves the lightharvesting capability, facilitates charge transport, and decreases charge recombination, while the triazine knots enable dipole-quadruple interactions with carbon dioxide so that the electron transfer from the skeleton to carbon dioxide is facilitated.…”
Section: Light-driven Carbon Dioxide Reductionmentioning
confidence: 94%
“…Then, Lan and co-workers developed a general approach to prepare a series of semiconductor-COF Z-scheme catalysts by integrating various semiconductors (TiO 2 , Bi 2 WO 6 , and a-Fe 2 O 3 ) with two COFs (Figure 3). 48 The composite systems enable the transfer of electrons generated by semiconductors to COFs through the covalent bond linkage. Electrons accumulate at the active sites of cyano and pyridine moieties of the COFs, leaving positively charged holes in the semiconductors for the acceptance of electrons from H 2 O during the CO 2 photoreduction.…”
Section: Metal Oxide/cof Compositesmentioning
confidence: 99%